2020
DOI: 10.2147/opth.s234008
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparison of the iLUX and the LipiFlow for the Treatment of Meibomian Gland Dysfunction and Symptoms: A Randomized Clinical Trial</p>

Abstract: Purpose: To compare the effects of eyelid treatment with the iLUX MGD Treatment System and the LipiFlow Thermal Pulsation System on objective and subjective parameters of meibomian gland function and symptoms. Patients and Methods: In this randomized, open-label, controlled, multicenter clinical trial, both eyes of 142 patients aged ≥18 years with Ocular Surface Disease Index (OSDI) scores ≥23, total meibomian gland scores (MGS) ≤12 in the lower eyelid of each eye, and tear break-up time (TBUT) <10 s were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(94 citation statements)
references
References 37 publications
7
87
0
Order By: Relevance
“…Only two studies (III) found an improvement in signs, such as MG secretion and BUT [ 39 , 41 ]. Other authors compared LipiFlow ® with other medical devices, such as Tauber et al [ 42 ] (I), who compared LipiFlow ® with iLux ® and did not find differences between the two treatments. Another study (II) reported that one single LipiFlow ® session was more effective in decreasing DED symptoms compared to 3 months of oral doxycycline [ 43 ].…”
Section: Warming Eyelid Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two studies (III) found an improvement in signs, such as MG secretion and BUT [ 39 , 41 ]. Other authors compared LipiFlow ® with other medical devices, such as Tauber et al [ 42 ] (I), who compared LipiFlow ® with iLux ® and did not find differences between the two treatments. Another study (II) reported that one single LipiFlow ® session was more effective in decreasing DED symptoms compared to 3 months of oral doxycycline [ 43 ].…”
Section: Warming Eyelid Devicesmentioning
confidence: 99%
“…An inner pad slips behind the eyelid and an outer pad is pressed against the outer surface of the eyelid [ 58 ]. As mentioned above, a clinical trial (I) compared the effectiveness of LipiFlow ® and iLux ® , without finding differences [ 42 ].…”
Section: Massaging and Light-based Devicesmentioning
confidence: 99%
“…Multiple studies have detailed the benefits of this technology and we are not going to cover those in this review [31][32][33][34]. Tuber., et al have done an excellent review of both technologies and found both systems to be equally beneficial in statistically improving meibomian gland function yet with no statistically significant difference between the two technologies [35].…”
Section: Thermal Pulsation (N-48)mentioning
confidence: 99%
“…The gland ducts become clogged, initially with overly viscous meibum and in chronic conditions as a result of keratinized cells on the duct margin. The traditional treatment of MGD has ranged from warm compresses and lid scrubs to topical or systemic pharmaceutical therapy, but in recent years new devices to warm the lids and/or to manually express viscous meibum have been developed [6][7][8].…”
Section: Introductionmentioning
confidence: 99%